A Conceptual Analysis of the Interconnection between Neuroscience and Spirituality in Islamic Religious Education - Qurrata A’yun; Hamka; Gusnarib (Journal of Contemporary Islamic Education, 2026)
The 21st century is marked by a moral crisis, technological disruption, and the fragmentation of meaning that challenge Indonesian education towards the Golden Generation of 2045; Islamic Religious Education needs to integrate scientific rationality and transcendental spirituality based on neuroscience and spirituality. This study aims to conceptually and comparatively analyze scientific findings related to the relationship between neuroscience and spirituality and its relevance in Islamic Religious Education learning, as well as to formulate theoretical contributions for the development of an integrative paradigm. This study uses a qualitative approach with a conceptual A Conceptual Analysis-based literature study. The data sources come from reputable journal articles, academic books, and relevant research results published in the last ten years. The data collection technique was carried out through documentation and scientific database searches, while data analysis used content analysis and thematic synthesis techniques. Data validity was maintained through source triangulation and referential credibility tests. The results of the study indicate that the integration of neuroscience and spirituality strengthens the understanding of the mechanisms of religious consciousness formation, empathy, and emotional regulation in learning. Conceptually, this interconnection encourages the transformation of Islamic Religious Education towards a holistic-inclusive approach based on brain development and spiritual experience. The implications affirm the theoretical contribution to the development of an integrative paradigm as well as the practical contribution to a more reflective, humanistic, and transformative learning design.